An attack on two fronts: predicting how changes in land use and climate affect the distribution of stream macroinvertebrates. (22nd April 2015) - Kuemmerlen, Mathias; Schmalz, Britta; Cai, Qinghua; Haase, Peter; Fohrer, Nicola; Jähnig, Sonja C.
Summary Global environmental change entails not only climatic alterations, but also changes in land use. Freshwater ecosystems are particularly sensitive to both of these changes, and their sustainable management requires better information on likely responses. To examine the effects of climate and land use on the freshwater community, the distributions of stream macroinvertebrates of the Changjiang catchment in south‐east China were modelled. The present distributions of 72 taxa were predicted using environmental variables generated by regional climate, land‐use and hydrological models. Hydrological predictors, sensitive to both climate and land use, were the most relevant predictors in the species distribution models (SDMs), followed by land use. The stream macroinvertebrates' distributions were then projected for the period 2021 to 2050 using three different future scenarios: (i) climate change, (ii) land‐use change and (iii) climate and land‐use change combined. Land‐use change was predicted to have the strongest negative impact on the community, with reductions in local richness (−20%), predicted diversity (−0.3%) and range size (−25%) and a general shift towards higher altitudes (+12%). The climate‐change scenario had a negative effect on predicted diversity (−0.1%) and resulted in a moderate altitudinal shift (+3%) along with increased richness (+15%) and range size (+19%). In the combined scenario, climate and land‐use changes counterbalanced each other to a certain degree, but had an overall detrimental effect. The results underscore the high relevance of land‐use change in future distribution predictions, exemplify the possible effect of interactions between land use and climate on hydrology and indicate how such responses can vary among freshwater taxa. The model also allows the detection of key environmental variables, the identification of vulnerable species and the definition of their potential distributions. This information is essential to establishing effective management and conservation strategies and gives a more comprehensive insight into the possible effects of global environmental change on freshwater ecosystems.